Comparing Pupil Light Response Modulation between Saccade Planning and Working Memory. Issue 1 (26th June 2018) - Wang, Chin-An; Huang, Jeff; Yep, Rachel; Munoz, Douglas P.
The signature of spatial attention effects has been demonstrated through saccade planning and working memory. Although saccade planning and working memory have been commonly linked to attention, the comparison of effects resulting from saccade planning and working memory is less explored. It has recently been shown that spatial attention interacts with local luminance at the attended location. When bright and dark patch stimuli are presented simultaneously in the periphery, thereby producing no change in global luminance, pupil size is nonetheless smaller when the locus of attention overlaps with the bright, compared to the dark patch stimulus (referred to as the local luminance modulation). Here, we used the local luminance modulation to directly compare the effects of saccade planning and spatial working memory. Participants were required to make a saccade towards a visual target location (visual-delay) or a remembered target location (memory-delay) after a variable delay, and the bright and dark patch stimuli were presented during the delay period between target onset and go signal. Greater pupil constriction was observed when the bright patch, compared to the dark patch, was spatially aligned with the target location in both tasks. However, the effects were diminished when there was no contingency implemented between the patch and target locations, particularly in the memory-delay task. Together, our results suggest the involvement of similar, but not identical, attentional mechanisms through saccade planning and working memory, and highlight a promising potential of local pupil luminance responses for probing visuospatial processing.